Incorporation of chlorhexidine and nano-sized sodium trimetaphosphate into a glass-ionomer cement: Effect on mechanical and microbiological properties and inhibition of enamel demineralization - da Silva, Márjully Eduardo Rodrigues [UNESP]; Danelon, Marcelle [UNESP]; Santos Souza, José Antonio [UNESP]; Silva, Dinah Fressato [UNESP]; Pereira, Jesse Augusto [UNESP]; Pedrini, Denise [UNESP]; de Camargo, Emerson Rodrigues; Botazzo Delbem, Alberto Carlos [UNESP]; Duque, Cristiane [UNESP] (Elsevier, 2019)
Objective: To evaluate the antimicrobial/antibiofilm and mechanical properties, and the effect on enamel demineralization of a resin-modified GIC (RMGIC) containing CHX and nano-sized sodium trimetaphosphate (TMP). Methods: RMGIC was associated with CHX (1.25 or 2.5%) and/or TMP (7 or 14%). Antimicrobial and antibiofilm activity were assessed using agar diffusion test and evaluation of biofilm metabolism, respectively. In addition, fluoride (F) and TMP releases as well as the diametral tensile (DTS) and compressive (CS) strength were determined. The percentage of mineral loss (%SH), integrated loss of subsurface hardness (ΔKHN) and enamel F concentrations were also evaluated. Results: RMGICs containing CHX associated or not with TMP presented higher inhibition zones and effect on S. mutans biofilm. A reduction on CS was observed only for RMGIC + 2.5%CHX and on DTS for RMGIC + 2.5%CHX + 14%TMP. The highest F and TMP releases and lowest %SH and ΔKHN values were detected for RMGIC + 1.25%CHX + 14%TMP and RMGIC + 2.5%CHX + 14%TMP. Higher enamel F concentrations were observed for TMP groups. Conclusion: 1.25%CHX and 14%TMP increased antimicrobial/antibiofilm action and the ability to prevent enamel demineralization, with minimal effect on the mechanical properties of RMGIC. Clinical significance: RMGIC containing CHX and TMP is an alternative material for patients at high risk for dental caries and can be indicated for low-stress regions or provisional restorations.
Keywords: Antimicrobial action; Chlorhexidine; Enamel demineralization; Glass ionomer cement; Phosphates